Two Approximation Formulas for Gamma Function with Monotonic Remainders - Mansour Mahmoud; Hanan Almuashi (Mathematics, 2024)
In this paper, two new approximation formulas with monotonic remainders for the gamma function have been presented. Also, we present some numerical comparisons between our new approximation formulas and some known ones, which demonstrate the superiority of our results.